FACTORS THAT INFLUENCE ATTITUDE IN PURCHASING FAKE PRODUCTS - Qurrata A'yun; Heriyana; Muchsin; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Study This aim For see Influence of Brand Image , Social Influence and Price Against Attitude in Purchasing Product False . Retrieval technique sample in study This is Purposive Sampling . Deep sample study This are 140 consumers who use it product fake in Lhokseumawe City . Primary data in study This taken with method interview and distribute questionnaire , Analytical tools used is method analysis multiple linear regression , test assumptions classic , instrument test ( validity and reliability ), testing hypothesis , and coefficient determination with using the SPSS version 25 program. Research results show that variable brand image (X1) influential positive significant to attitude (Y ), social influence variable (X2) influential positive significant to attitude (Y) and price (X3) have a significant negative effect to attitude (Y).